Keanekaragaman Ikan yang Bernilai Ekonomi dan Kandungan Logam Berat Pb dan Cd pada Ikan Sapu-Sapu di Sungai Bedadung Jember - Munandar, Kukuh; Eurika, Novy (Universitas Sebelas Maret, 2016)
Water of river Bedadung in urban areas used by the local community for bathing, washing and toilet, and dispose of garbage and waste can be observed during the dry season. Whereas water of river Bedadung used by the Regional Water Company (PDAM) Jember as a raw water source in the areaÂ ofÂ Villa Tegal Besar estate District of Kaliwates. Besides the existing fish used for consumption by the public, both for their own consumption or for sale. The qualitative research with quantitative descriptive design. Location of research conducted by purposive sampling, the location of sampling carried out on three stations, namely: 1) Station 1 is located around the bridge Jl. Mastrip District of Sumbersari, 2) Station 2 is located in the vicinity of the bridge Jl. Ahmad Yani District of Sumbersari (or better known as the bridge